Analisis Hubungan Pelaksanan Supervisi Dengan Pengetahuan Perawat Dalam Pemakaian Dressing Transparan - Delvy, Rasymi (REAL in Nursing Journal, 2022)
Background: The incidence of phlebitis is a health problem both worldwide and in Indonesia, and the highest infectious disease in health services. The quality committee in the prevention of phlebitis is looking for a solution through the FMEA method which recommends that the solution is to supervise the implementing nurses, but the incidence of phlebitis has not decreased. This study aims to analyze the relationship between the implementation of supervision and the knowledge of nurses in the use of transparent dressings in an effort to prevent phlebitis at RSI Ibnu Sina Padang. Methods: This study uses a descriptive analytic design with a sample of 55 nurses. Non-probability sampling sampling technique, then categorized. The dependent and independent variables were analyzed using the chi square test. The univariate test showed that most of the nurses were in early adulthood and almost all of the nurses were female. When viewed from the level of education, most of them are qualified nurses and have >5 work. Results: From statistical testThe results of the analysis of the relationship between the implementation of supervision and the knowledge of nurses showed that 33 nurses perceived that the implementation of supervision was good, but 9 (27.30%) had poor knowledge. Bivariate test shows the value ofp-value =0.007, it shows that there is a significant relationship between the implementation of supervision and the knowledge of nurses. The analysis is also known to have OR = 5.17, meaning that the nurse's knowledge increases 5 times if the implementation of supervision is good. Conclusion: It is hoped that the management will carry out regular supervision of implementing nurses so that they can increase knowledge in efforts to prevent phlebitis.